2016
DOI: 10.7287/peerj.preprints.967v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptual category learning of photographic and painterly stimuli in rhesus macaques (Macaca mulatta) and humans

Abstract: Humans are highly adept at categorizing visual stimuli, but studies of human categorization are typically validated by verbal reports. This makes it difficult to perform comparative studies of categorization using non-human animals. Interpretation of comparative studies is further complicated by the possibility that animal performance may merely reflect reinforcement learning, whereby discrete features act as discriminative cues for categorization. To assess and compare how humans and monkeys classified visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This might be the result of several factors, like differences in stimulus size and relative difference between luminance of stimuli and background. Our stimuli are also much more complex and may require higher cognitive load (Altschul et al, 2017;Tatler & Melcher, 2007), which is known to cause pupil dilation (Beatty, 1982;Hess & Polt, 1964;Just & Carpenter, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be the result of several factors, like differences in stimulus size and relative difference between luminance of stimuli and background. Our stimuli are also much more complex and may require higher cognitive load (Altschul et al, 2017;Tatler & Melcher, 2007), which is known to cause pupil dilation (Beatty, 1982;Hess & Polt, 1964;Just & Carpenter, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we measured the pupil response to artistic paintings representing scenes with a visible sun, a visible moon, or the presence of diffused light to address the effect of cognitive interpretation of very complex stimuli. In fact, paintings render a scene through the artist's mind, requiring an even higher level of interpretation compared with photographs or artificial stimuli (Altschul, Jensen, & Terrace, 2017;Tatler & Melcher, 2007). In addition to the effect of image content, we also investigated the effect of contextual information, such as color and global layout.…”
Section: Introductionmentioning
confidence: 99%
“…It was therefore highly unlikely that subjects would see the same image more than once within an interval of several hundred trials. Stimuli from the first four categories were previously used by Altschul et al (2016) with a different set of subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Can animals, for example, treat categories as though they were informative stimuli, signaling appropriate behavior in a cognitive task? Altschul et al (2016) demonstrated that rhesus macaques cannot only distinguish between four simultaneously presented categories of stimuli, but that they can also learn their serial order using a variant of the simultaneous chain task (Terrace, 1984(Terrace, , 2005. This suggests that animals cannot only learn to identify categories but they can also process categories in the same way they can process single stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation